Realizing Safe Schools: Legal Strategies in Tackling Violence among Students - Medan, Karolus Kopong (PT. Hafasy Dwi Nawasena, 2024)
This study aims to analyze various legal strategies that can be applied in dealing with violence in schools, with a focus on stricter prevention and law enforcement efforts. The main objective of this study is to provide policy recommendations that can assist authorities in creating a safer and more supportive school environment for students. The method used in this study is Systematic Literature Review (SLR), which aims to collect, assess, and analyze various relevant literature on violence in schools and legal strategies to address it. Through this approach, the data obtained will provide a clearer picture of the policies that have been implemented and their effectiveness. The results of the study are expected to provide deeper insights into legal steps that need to be strengthened in overcoming violence in schools. In addition, this research also aims to produce recommendations that can be applied by schools, the government, and the community in an effort to create a safer, healthier, and violence-free learning environment.